PENGARUH IMPLEMENTASI SISTEM INFORMASI AKUNTANSI MANAJEMEN (SIAM), DESENTRALISASI, DAN KEJELASAN SASARAN ANGGARAN TERHADAP KINERJA PENYUSUNAN ANGGARAN KABUPATEN EMPAT LAWANG - febrianty febrianty; jovan febriantoko (Jurnal Ilmiah Ekonomi Dan Bisnis, 2017)
Abstract: The purpose of this research is to test and analyze the empirical evidence of the influence of management accounting information system implementation, decentralization, and clarity of budget targets to the performance of budget preparation of Regency of Empat Lawang. The study design is a causal or causal research. The type of data used in the form of primary data, namely in the form of questionnaires and partly done also with interviews directly. The sampling technique is purposive sample, with criteria: the employee working in the government environment of Empat Lawang Regency who served as Secretary / Secretary of SKPD, Head of Division / Head of Division, and Head of Section / Sub Head of Sub Division (Kasubid) who served in secretariat Regions, agencies, offices, bodies, and local technical institutions. The sample obtained is 204 SKPD apparatus from 36 SKPD in Empat Lawang District. SKPD apparatus that returned the questionnaire as many as 158 SKPD apparatus, meaning that the questionnaire processed as many as 158 questionnaires (no questionnaire data defects). The results achieved in this study are: The first hypothesis in this study which states that there is influence implementation of Management Accounting Information System (SIAM) on the performance of budget preparation at the local government of Empat Lawang Regency, accepted. The second hypothesis, there is the effect of decentralization on the performance of budget preparation at the local government of Empat Lawang Regency, rejected. The third hypothesis, there is the influence of clarity of budget targets on the performance of budget preparation at the regional government of Empat Lawang Regency, accepted. The fourth hypothesis, simultaneously the implementation of SIAM, decentralization, and clarity of budget targets had a significant effect on the performance of budget preparation at the local government of Empat Lawang Regency, accepted.Keywords: SIAM, decentralization, budget, performance, Four Lawang